Geneza i działalność Światowej Organizacji Handlu (WTO) na arenie międzynarodowej - Stępień-Załucka, Beata (My University, 2015)
The World Trade Organization was created as one of the final effects of GATT on 15 Apr. 1994. At present, it has 151 members. The membership is primarily conditioned by economic conditions, which results from the fact that WTO can be undoubtedly recognized as one of leadingorganizations affecting the world economy and trade. Its peculiarity and exceptional character are expressed not only by diversity of members, as it groups both developed and developing countries, but also through a range of outstanding economic achievements. The main goal of WTO activity is undertaking actions that would fruit on the international forum with enhancement of life standards, provision of full employment, increase in real incomes, effective demand, and development of manufacturing and trade of goods and services with optimal use of world resources, with maintenance of environment, and considering its protection.
ORIGIN AND ACTIVITY OF THE WORLD TRADE ORGANIZATION ON THE INTERNATIONAL FORUM